Digital Comic Media Development to Overcome Students’ Difficulty in Learning Figurative Language Grade V Elementary School - A'yun, Nurul; Sukardi, Sukardi (JETL (Journal of Education, Teaching and Learning), 2024)
Figurative language as one of the materials in Indonesian language learning, is very important to learn. However, there are still many students who have difficulty understanding the material. Difficulty understanding the material will result in difficulty understanding the meaning of words. This study aims to develop digital comic media on figurative language material for grade V elementary school students. This type of research is development research with the ADDIE development model. The data collection techniques used in this research are observation, interviews, documentation, questionnaires, and tests. The data analysis techniques used were the normality test, t-test, and N-Gain test. The results of the assessment of the feasibility of digital comics from material experts obtained a score of 89.87%. While the assessment of media experts obtained a value of 88.05%. In addition, responses from users on small-scale product trials obtained a percentage of 98.33% from students and 100% from homeroom teacher. Meanwhile, during the large-scale product trial, a percentage of 98.18% was obtained from students and 100% from homeroom teacher. The effectiveness of digital comics on figurative language material is evidenced in the t-test, with the results in the small-scale product trial a value of ?  of 11.366 >  with a value of 2.571. While in the large-scale product trial obtained  amounting to 16.115 >  with a value of 2.080. In the N-Gain test, the small-scale product trial obtained an N-Gain of 0.77 and the large-scale product trial obtained an N-Gain of 0.74.